Analisis Etika Profesi Hakim Dalam Pengambilan Keputusan Hukum - Muhammad Hanafi Nasution, Rika Sari, Andri Nurwandri, Alfina Sugiarni, Bayu Pamungkas, Defito Adlin, (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
A judge's professional attitude is not only seen as competent, intellectual and successful in his field of justice, but behavioral aspects are also part of the assessment that must be carried out in implementing the code of ethics. Judges to ensure respect for law and justice. In the world of justice, it is very important for judges who are responsible for applying the law to have professional ethics. The code of ethics must be a guideline for judges in carrying out their professional duties so that they are devoted to God Almighty, fair, wise/authoritative, ethical and honest in examining, deciding and resolving cases.